Delayed Bladder Perforation Related to Immediate Single Dose Intravesical Doxorubicin Instillation After TURBT: A Case Report and Literature Review - Alrabadi, Adel (Clin Med Insights Case Rep, 2021)
INTRODUCTION: Intravesical chemotherapy instillation immediately after tumor resection is a well-known practice in the management of non-muscle invasive bladder cancer. Despite being largely well tolerated in most cases, it is not devoid of severe and life-threatening complications. CASE PRESENTATION: We present an unusual case of bladder perforation that happened 2 weeks after bladder tumor resection. The patient had received single dose intra-vesical instillation of doxorubicin after TUR-BT. Conservative managements failed to achieve bladder healing; as a result, open surgical repair was performed. To the best of our knowledge, this is the first reported case of bladder perforation after intra-vesical doxorubicin instillation. CONCLUSION: The occurrence of such a rare serious complication in a mostly safe intervention must be taken into consideration. A high index of suspicion, timely management, and proceeding to more invasive surgical treatments when necessary are cornerstones in the management and preserving the bladder.